2013
DOI: 10.1016/j.pnpbp.2013.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GABA levels in anterior cingulate cortex/medial prefrontal cortex in panic disorder

Abstract: Changes of various brain metabolites including γ-aminobutyric acid (GABA), measured by 1H-magnetic resonance spectroscopy (MRS), have been reported in panic disorder (PD). Deficits in GABA have been implicated in the pathophysiology of PD. Furthermore, it has been suggested that cortical metabolite changes in PD are familial. Eleven PD patients, including five with and six without a PD family history, and eight age- and gender-matched healthy controls without a family history of psychopathology were recruited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 30 publications
6
46
0
Order By: Relevance
“…In this study, lower GABA + levels in occlusal splint DLPFC subjects suggest that anxiety-related circuits (49, 60) that may affect possible bruxism were less inhibited than in controls (Table 1). Decreased frontal lobe GABA levels have also been detected in panic disorder individuals (42) albeit in the medial rather than dorsolateral prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, lower GABA + levels in occlusal splint DLPFC subjects suggest that anxiety-related circuits (49, 60) that may affect possible bruxism were less inhibited than in controls (Table 1). Decreased frontal lobe GABA levels have also been detected in panic disorder individuals (42) albeit in the medial rather than dorsolateral prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…As determined by recent MRS studies (39, 40), GABA plays an important role in the pathophysiology of human anxiety disorders such as panic disorder and PTSD (41). Goddard et al discovered lower than normal cortical GABA levels in panic disorder individuals (42, 43). The etiology of oral dysfunctions such as bruxism and TMD is multifactorial and psychological factors are considered a major component in the initiation and progression of these disorders (21), which suggests that GABA neuronal system may also be critical in the manifestation of bruxism.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, evidence of low GABA in the ACC and medial PFC, was reported in a third study of patients with panic disorder. Notably, in that study, GABA differences were more pronounced in individuals with a family history of panic disorder (Long, et al, 2013). Less data are available from patients with other types of anxiety disorders, although thalamic GABA was lower in patients with social anxiety disorder (Pollack, et al, 2008) and medial PFC GABA was lower in patients with OCD (Simpson, et al, 2012).…”
Section: Translating To the Human Condition: In Vivo Gaba Mrs Studiesmentioning
confidence: 61%
“…Accordingly, characterizing the ontogeny of multiple neurotransmitter systems has been the subject of numerous investigations (for review, see (Spear, 2000), however more recently, investigation into the development of the inhibitory neural system, γ-amino-butyric acid (GABA), is gaining significant attention as a potential moderator of human developmental changes in impulse control, self-regulation and decision-making (Silveri, et al, 2013). Parallel to studies investigating contributions of brain GABA to functioning during adolescence is an accumulation of GABA findings based on studies conducted in healthy adults (Boy, et al, 2010; Goto, et al, 2010; Northoff, et al, 2007; Stagg, 2013; Sumner, Edden, Bompas, Evans, & Singh, 2010) and in adult patients with psychiatric illnesses (Bhagwagar, et al, 2008; Ham, et al, 2007; Long, et al, 2013; Plante, Jensen, Schoerning, & Winkelman, 2012a; Pollack, Jensen, Simon, Kaufman, & Renshaw, 2008; Rosso, et al, 2013; Simpson, et al, 2012; Streeter, et al, 2005; Yoon, et al, 2010). Notably, the role of GABA in alcohol responsiveness has been well established in animal models, and GABA-related alterations have been investigated in humans with alcohol abuse disorders (Abe, et al, 2012; Behar, et al, 1999; Mason, et al, 2006; Mon, Durazzo, & Meyerhoff, 2012; Silveri, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of genetically mediated GABAergic signaling patterns in PD is needed. Recent magnetic resonance spectroscopy by Long et al (2013) showed significantly lower cortical GABA levels in PD patients than controls, with more exaggerated deficits among patients with a family history of PD.…”
Section: Genetic Association With Gabrb3 Expression In Ceph Triosmentioning
confidence: 96%